Economic, ecological, and social dimensions of industrial enterprises environmental security and sustainability ensuring - Mashchenko, Maryna; Serhiienko, Olena; Tatar, Maryna; Klimenko, Olena; Tiesheva, Larysa; Kamelchuk, Yuriy (Fintechalliance, 2025)
Industrial enterprise environmental security assessment refers to the assessment and analysis of industrial environmental security measures and vulnerabilities to protect against potential threats and risks to the environment. By conducting an environmental security assessment, industrial companies can proactively identify and eliminate security gaps, reduce the potential impact on the environment, and ensure compliance with regulatory acts. The article's purpose is to assess the industrial enterprises' environmental security level, transform strategies to reduce environmental risks, and formulate recommendations for simultaneously increasing economic and environmental security. Our study presents an improved structured methodology for constructing an environmental security indicator system for industrial enterprises. Unlike conventional approaches, the proposed method follows a systematic sequence that includes defining the objectives and diagnostic tasks, collecting and processing relevant data, and ultimately forming a comprehensive indicator system. Central to this approach is the development of an integral indicator that reflects the overall level of environmental security. This indicator is derived from a balanced set of socio-economic, technical-technological, scientific-innovative, and managerial-organizational dimensions, incorporating both internal and external factors influencing enterprise operations. The uniqueness of the proposed model lies in its use of a geometric mean to synthesize integral indicators across the economic, ecological, and social domains, while accounting for the relative significance of each component. This weighting mechanism ensures a more accurate and nuanced assessment by recognizing the differential impact of individual indicators on overall environmental security. The level of environmental security was calculated for three companies in the railway transport industry. Also, we form the strategies to mitigate environmental risks, which allow the industrial enterprises to enhance both economic resilience and ecological integrity, and to improve their overall security. In addition, we proposed recommendations for simultaneously improving the economic and environmental security of industrial enterprises.

Оцінка екологічної безпеки промислових підприємств стосується оцінки й аналізу заходів промислової екологічної безпеки та вразливостей для захисту від потенційних загроз і ризиків для навколишнього середовища. Проводячи оцінку екологічної безпеки, промислові підприємства можуть проактивно виявляти й усувати прогалини в безпеці, зменшувати потенційний вплив на навколишнє середовище та забезпечувати дотримання нормативних актів. Метою дослідження є оцінка рівня екологічної безпеки промислових підприємств, трансформація стратегій для зменшення екологічних ризиків і формування рекомендацій для одночасного підвищення економічної та екологічної безпек. Наше дослідження пропонує вдосконалену структуровану методологію побудови системи показників екологічної безпеки для промислових підприємств. На відміну від традиційних підходів, запропонований метод дотримується систематичної послідовності, яка включає визначення цілей і діагностичних завдань, збирання та обробку відповідних даних і зрештою формування комплексної системи показників. Центральним у цьому підході є розробка інтегрального показника, що відображає загальний рівень екологічної безпеки, який виводиться зі збалансованого набору соціально-економічних, техніко-технологічних, науково-інноваційних та управлінсько-організаційних вимірів, що включає й внутрішні, і зовнішні фактори, які впливають на діяльність підприємства. Унікальність запропонованої моделі полягає у використанні геометричного середнього для синтезу інтегральних показників в економічній, екологічній та соціальній галузях, ураховуючи при цьому значущість кожного компонента. Цей механізм зважування забезпечує більш точну та нюансовану оцінку, враховуючи різний вплив окремих показників на загальну екологічну безпеку. Рівень екологічної безпеки було розраховано для трьох компаній залізничної транспортної галузі. Також ми сформували стратегії пом'якшення екологічних ризиків, які дозволяють промисловим підприємствам підвищити й економічну стійкість, і екологічну цілісність та покращити свою загальну безпеку. Крім того, ми запропонували рекомендації для одночасного покращення економічної та екологічної безпек промислових підприємств.
Економічні, екологічні та соціальні виміри забезпечення екологічної безпеки та сталого розвитку промислових підприємств
Keywords: economic security; environmental security; environmental security management process; industrial enterprises; interaction; strategies; економічна безпека; екологічна безпека; процес управління екологічною безпекою; промислові підприємства; взаємодія; стратегії